Effects of Shrimp Meal Fermented with Aspergillus niger On Physical Quality of Broiler Meat - Djalal Rosyidi; Agus Susilo; Rachmat Muhbianto (Jurnal Ilmu dan Teknologi Hasil Ternak (JITEK), 2009)
The research materials were 75 broiler chickens of 1 day old and feeds. The research employed five treatments, namely (P0: feed without addition of fermented shrimp meal, P1: feed with 5 % addition of fermented shrimp meal, P2: feed with 7.5 % addition of fermented shrimp meal, P3: feed with 10 % addition of fermented shrimp meal, P4: feed with 12.5 % addition of fermented shrimp meal. Every treatment was repeated 3 times, with 5 chickens respectively. Variables of this research were Water Holding Capacity (WHC), cooking loss and tenderness of broiler meat. Data were analyzed by completely randomized design, if there was a significant effect, it was followed by Duncanâ€™s Multiple Range Test (DMRT). The result of this research showed that the use of fermented shrimp meal in broiler feed can improve WHC, degrading cooking loss and improving tenderness of broiler meat. Â  Keywords : Water holding capacity, cooking loss, tenderness